Pengaruh Kualitas Pelayanan Terhadap Loyalitas Nasabah Bank Syariah (Studi Pada Masyarakat Eks Karesidenan Surakarta) - Sriyanto, Bambang; Sumadi, Sumadi; Thoin, Muhammad (ITB AAS INDONESIA Surakarta, 2024)
Global technological developments make business competition increasingly competitive. The emergence of competitors in the same industry poses a threat to companies running their business. Ease of access to banking facilities makes it easy for consumers to differentiate the quality of bank services from other banks. For this reason, Islamic banking is competing fiercely to improve the quality of its services so that customer loyalty can be achieved. Facts have been found that customer loyalty can increase competitiveness. The role of customer loyalty is very crucial for companies, many experts examine the important contribution of customer loyalty to companies. The aim of this research is to find out whether service quality (Reliability, Guarantee, Physical Evidence, Empathy and Responsiveness) influences loyalty in Sharia Banks in the Surakarta Residency area. The research method uses quantitative primary data, multiple linear regression analysis approach and the SPSS program. From the test results, the number of respondents for this study was 75 respondents. These findings show that Reliability, Guarantee and physical evidence do not have a significant effect on Loyalty, while Empathy and Responsiveness have a significant effect on Loyalty in the former Surakarta Residency area.